Implementasi Konsep Tri Hita Karana Dalam Penguatan Bhinneka Tunggal Ika Di Lingkungan Perguruan Tinggi - Luh Intan Purnama Dewi; Nadia Aurelia Tasya Putu (Universitas Pendidikan Ganesha, 2020)
Indonesia is synonymous with ethnic, cultural, linguistic and religious diversity. The motto of Bhinneka Tunggal Ika is always upheld to maintain unity amidst the differences in this nation. However, the current condition of Indonesian society shows that the human value in the civilization of the development of the Indonesian nation has experienced distortion. The actions taken also tend to contradict the motto of Bhinneka Tunggal Ika. The Tri Hita Karana concept is here to help foster awareness and tolerance in society, both towards God, fellow humans and the environment. This research was made using a type of normative research which is presented in a descriptive-prescriptive form. Based on the data collected, it is known that the cultivation and implementation of the Tri Hita Karana concept in the university environment is important to do, especially as students as agents of change can determine the progress of their country. In addition, Tri Hita Karana and Bhinneka Tunggal Ika also have a close relationship, where the two concepts harmonize with each other and can form awareness and tolerance in this multicultural society.